Trade, tariffs, growth and poverty - Ackah, Charles; Leyaro, Vincent; Morrissey, Oliver (Edward Elgar Publishing, 2015)
Increased globalization and widespread trade liberalization in developing countries since the 1980s has inspired considerable debate on the impact of globalization in general, and trade liberalization in particular, on growth, incomes and poverty. This chapter provides an overview of the issues and evidence in a selective literature review. After considering why trade is important and arguments for and against protection in the remainder of this section, we focus on three issues. Section 2.2 provides an overview of the literature on the relationship between trade and growth, noting that whilst a positive correlation is well established it is difficult to assert ‘causality’ (whether trade drives growth or growth leads to increased trade). Section 2.3 addresses the related issue of how trade liberalization (trade policy reforms reducing barriers to trade, especially on imports) affects growth, for which the evidence is less clear. Section 2.4 considers the broader issue of how trade relates to poverty, especially in low-income countries (LICs) or sub-Saharan Africa (SSA). Section 2.5 provides a very brief conclusion. Economists disagree about many things, but one proposition that attracts widespread agreement is that high barriers to trade damage the economy, especially if there is considerable variation across sectors and products in the extent of barriers (as this induces prices distortions that generate inefficiency).